All-solid-state calcium ion selective electrode suitable for concrete
Through the all-solid calcium ion selective electrode, the Fe3O4@CNTs transducing layer and calcium ion selective membrane are used to solve the problem that the prior art cannot directly detect calcium ions in concrete, achieving high-precision and rapid calcium ion detection, supporting the assessment of the risk of concrete dissolution and reinforcement corrosion.
Patent Information
- Application Number
- CN202411682132.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing calcium ion sensors cannot be directly used for the detection of calcium ions in concrete, and the existing methods consume time and have low accuracy, so they cannot monitor the concrete dissolution in situ.
The all-solid calcium ion selective electrode is adopted, including wires, electronic conductors, Fe3O4@CNTs transducing layer, calcium ion selective membrane and shell. Through the combination of Fe3O4@CNTs transducing layer and calcium ion selective membrane, high-precision detection of calcium ion concentration in concrete is achieved.
It has achieved high precision and rapid detection of calcium ion concentrations in high alkalinity and complex environments of various ions, and can monitor calcium ion concentrations at different depths in concrete structures in real time, and evaluate the degree of concrete dissolution and the risk of steel bar corrosion.
Smart Images

Figure CN119534587A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building sensors, in particular to hydraulic structures, and is a fully solid calcium ion selective electrode suitable for use in a concrete dissolution environment. Background Art
[0002] Concrete is the most widely used and used building material in the world today. It is composed of cementitious materials that connect block and granular materials into a whole through their own physical and chemical effects, and has a certain strength. For concrete structures such as dams, gate piers, bridge piers, tunnel linings, etc. that are in contact with water for a long time, the concrete materials will undergo dissolution erosion (dissolution) under the action of water media, that is, the solid phase components of the hardened cement stone gradually dissolve, resulting in the destruction of the integrity of the concrete. Among the hardened cement stone, the cement hydration product calcium hydroxide has the highest solubility. Under the action of running water, calcium hydroxide gradually dissolves, the porosity of the cement stone increases, and the alkalinity inside the concrete decreases; the hydration products of high-calcium cement decompose to compensate for the reduced alkalinity, which ultimately leads to a decrease in strength and structural damage. Therefore, the change in the calcium oxide content in the liquid phase of concrete is an important indicator for assessing the degree of concrete dissolution.
[0003] For reinforced concrete structures, a dense passive film is formed on the surface of the steel bar in high-alkalinity concrete, which plays a role in protecting the steel bar. When the alkalinity of concrete drops to a certain value, the passive film on the surface of the steel bar cannot exist stably, and the risk of steel bar corrosion increases. Therefore, the change in calcium oxide content in the liquid phase of concrete is an important indicator for assessing the risk of steel bar corrosion and structural safety.
[0004] At present, the determination of concrete dissolution degree mostly adopts EDTA titration method, or colorimetric method using indicator to observe the color change of sample section. In addition, the mass loss rate, calcium ion dissolution and microscopic detection are used to judge the degree of concrete dissolution. These methods are usually time-consuming, low in accuracy, and unable to monitor the concrete dissolution in situ.
[0005] Calcium ion sensors can detect calcium ions in liquid samples quickly, simply, accurately and economically. The calcium ion sensors currently available on the market are mainly used in biology, ecological environment, and industrial fields, such as changes in calcium ion concentrations in cells, calcium ion concentrations in blood, and calcium ion concentrations in milk. The pH value of the sample to be tested is usually required to be within the range of (4 to 10). There are also requirements for the working temperature. Cement concrete is a highly alkaline material, usually with a pH value above 12.5, and contains a variety of ions in the liquid phase. Especially when the environmental medium is complex, in addition to the various ions of the concrete itself, the ions in the environmental medium will migrate into the concrete and interfere with the detection results. Summary of the invention
[0006] In view of the problem that existing calcium ion sensors cannot be directly used for the detection of calcium ions in concrete, the present invention provides an all-solid-state calcium ion selective electrode suitable for testing the calcium ion concentration in concrete.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0008] An all-solid-state calcium ion selective electrode suitable for concrete, comprising a conductor, an electronic conductor, a Fe3O4@CNTs transduction layer, a calcium ion selective membrane, a shell and a fixing material, wherein the conductor, the electronic conductor, the Fe3O4@CNTs transduction layer and the calcium ion selective membrane are sequentially connected from top to bottom into a whole and placed in the shell, and the upper section of the conductor is located outside the shell, and the upper section of the electronic conductor and the lower section of the conductor are encapsulated with the shell by a fixing material;
[0009] The lower end of the wire is connected to the upper end of the electronic conductor, the lower end of the electronic conductor is coated with Fe3O4@CNTs to form a Fe3O4@CNTs transduction layer, and the calcium ion selective membrane is loaded below the Fe3O4@CNTs transduction layer;
[0010] The preparation method of Fe3O4@CNTs comprises the following steps:
[0011] (1) Pour CNTs into acid for ultrasonic dispersion, pour into a reaction kettle, keep constant temperature at 55-65°C for 1-2 hours, and cool naturally to room temperature to obtain mixture I;
[0012] The acid in step (1) is nitric acid or a mixed solution of nitric acid and sulfuric acid, wherein the concentration of the acid is 0.45 to 0.55 mol / L;
[0013] The ultrasonic dispersion time in step (1) is 3 to 5 hours;
[0014] (2) treating the mixture obtained in step (1) with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and centrifuging the mixture when the pH value of the solution is between 6.5 and 7.5 to separate the solid matter from the deionized water, and vacuum drying the mixture to obtain CNTs;
[0015] The centrifugal speed in step (2) is 7000-9000 r / min;
[0016] The vacuum drying temperature in step (2) is 55-65°C;
[0017] (3) dissolving FeCl2·4H2O and SnCl4·5H2O in deionized water, then adding the CNT obtained in step (2), and ultrasonically dispersing for at least 10 min, and adding NaOH solution dropwise under vigorous stirring to obtain mixture II;
[0018] The concentration of the NaOH solution in step (3) is 2 mol / L;
[0019] The mass fractions of each raw material component in step (3) are:
[0020]
[0021] The above-mentioned NaOH mass fraction is the solubility in the NaOH solution.
[0022] And the molar ratio of Fe / Sn must be 2:1;
[0023] (4) transferring the mixture II obtained in step (3) to a reaction vessel to react and obtain a mixture III;
[0024] In step (4), the reaction temperature is 230-245° C. and the reaction time is 18-30 h;
[0025] (5) centrifuging the mixture III obtained in step (4) using a centrifuge, collecting the solid matter, washing it with deionized water for multiple times and vacuum drying it to obtain Fe3O4@CNT;
[0026] In step (5), the centrifugal speed is 7000-9000 r / min, and the centrifugal time is 10-15 min.
[0027] The preparation method of the calcium ion selective membrane is as follows: calcium ion carrier ETH5234, ion exchanger NaTFPB, polymer PVC matrix and plasticizer o-NPOE are added into a container, then redistilled THF is added, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration;
[0028] The mass fractions of each raw material component are as follows:
[0029]
[0030] Furthermore, the lower end of the wire and the upper end of the electronic conductor of the present invention are connected by high temperature welding or conductive adhesive bonding.
[0031] Furthermore, the fixing material of the present invention is epoxy resin.
[0032] Furthermore, the calcium ion selective membrane of the present invention has a thickness of 30 to 50 μm.
[0033] Furthermore, the Fe3O4@CNTs transduction layer of the present invention has a thickness of 50 to 100 μm.
[0034] Furthermore, the conductive wire of the present invention is preferably a copper wire.
[0035] Furthermore, the electronic conductor of the present invention uses copper rod electronic conductor, pretreated copper rod electronic conductor, metals such as platinum and gold, or glassy carbon electrode as the material of the electronic conductor.
[0036] Furthermore, the electronic conductor of the present invention is preferably a pretreated copper rod electronic conductor, and the pretreatment method of the copper rod electronic conductor includes: first using acetone to ultrasonically clean the copper rod electronic conductor for 10 to 15 minutes, then using 0.1 mol / L dilute hydrochloric acid solution to ultrasonically clean it for 10 to 15 minutes, then using deionized water to ultrasonically clean it for 10 to 15 minutes, and finally drying it.
[0037] Furthermore, the shell of the present invention is preferably made of PC material and is preferably tubular in shape.
[0038] The method for preparing the all-solid-state calcium ion selective electrode of the present invention specifically comprises the following steps:
[0039] (1) Connecting the upper end of the electronic conductor to the lower end of the wire;
[0040] (2) adding Fe3O4@CNTs to an organic solvent and dispersing by ultrasonic to obtain a uniform mixture; then coating the mixture on the lower end of the electronic conductor, and coating again after the organic solvent is completely volatilized; repeating the process 2-3 times to obtain a Fe3O4@CNTs transduction layer;
[0041] The organic solvent in step (2) is a mixture of DOP and 0.1% ethanol solution;
[0042] The amounts of the components in step (2) are: 20 parts by mass of Fe3O4@CNTs, 1 part by mass of organic solvent;
[0043] The ultrasonic dispersion time in step (2) is 30 to 40 minutes;
[0044] (3) loading the calcium ion selective membrane on the Fe3O4@CNTs transduction layer obtained in step (2);
[0045] (4) Finally, the wire, the electronic conductor, the Fe3O4@CNTs transduction layer, and the calcium ion selective membrane connected as a whole are placed in a shell, the upper section of the electronic conductor and the upper part are fixed to the inner wall of the shell by a fixing material, and the upper section of the wire is exposed outside the shell, thus obtaining the all-solid-state calcium ion selective electrode of the present invention.
[0046] The method for using the all-solid-state calcium ion selective electrode of the present invention is as follows:
[0047] For existing concrete buildings, a hole is drilled in the concrete to be tested in advance, the depth of the hole is the depth of the concrete to be tested, the above-mentioned all-solid-state calcium ion selective electrode is placed in the tube, and the electrode is fixed in a detachable manner, the bottom of the electrode shell is in contact with the bottom of the hole, and a solid reference electrode needs to be inserted to form a dual-electrode system, so that the concrete calcium ion concentration can be detected and monitored.
[0048] For new buildings, before pouring concrete, a certain length of tubes made of materials such as stainless steel and PC, with a diameter slightly larger than the maximum diameter of the electrode, with the bottom ends of the two tubes at an equal distance from each other, are pre-installed at the location to be tested as a mold, and the bottom of the tube is blocked with an easily removable non-absorbent rod, and then concrete is poured; after the construction is completed, the non-absorbent rod is taken out of the tube, and the above-mentioned all-solid-state calcium ion selective electrode is placed in the tube, and the electrode is fixed in a detachable manner, with the bottom of the electrode in contact with the bottom of the hole, so that the calcium ion concentration of the concrete can be detected and monitored.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] (1) The all-solid-state calcium ion selective electrode of the present invention has high calcium ion conductivity and selectivity, high electrical conductivity, stable electrode potential, and strong working performance.
[0051] (2) The all-solid-state calcium ion selective electrode of the present invention is suitable for the complex internal environment of concrete, such as high alkalinity and multiple ions, and is not affected by the service environment of concrete. The electrode potential fluctuates slightly and has high accuracy. For example, the high alkalinity of concrete, the presence and pressure of other ions that may exist, etc., will not interfere with the test results.
[0052] (3) The all-solid-state calcium ion selective electrode of the present invention can monitor the calcium ion concentration at different depths in the concrete structure in real time by using potential changes, thus providing a basis for evaluating the degree of concrete dissolution, the risk of steel bar corrosion and structural safety assessment.
[0053] (4) The all-solid-state calcium ion selective electrode of the present invention has a simple structure and process and is inexpensive to manufacture. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a schematic diagram of the structure of the all-solid-state calcium ion selective electrode of the present invention.
[0055] Figure 2 This is a relationship diagram between the electrode open circuit potential and the negative logarithm of the calcium ion concentration when the calcium ion selective membrane thickness of the all-solid-state calcium ion selective electrode described in Example 3 of the present invention is 50 μm.
[0056] Figure 3This is a relationship diagram between the electrode open circuit potential and the negative logarithm of the calcium ion concentration when the calcium ion selective membrane thickness of the all-solid-state calcium ion selective electrode described in Example 2 of the present invention is 40 μm.
[0057] Figure 4 This is a relationship diagram between the electrode open circuit potential and the negative logarithm of the calcium ion concentration when the calcium ion selective membrane thickness of the all-solid-state calcium ion selective electrode described in Example 1 of the present invention is 30 μm.
[0058] Figure 5 This is a chronopotentiometry spectrum of the all-solid-state calcium ion selective electrode described in Example 3 of the present invention.
[0059] Figure 1 The labels in the figure are: 1 conductor, 2 electron conductor, 3 Fe3O4@CNTs transduction layer, 4 calcium ion selective membrane, 5 shell, 6 fixing material. DETAILED DESCRIPTION
[0060] Embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. For the sake of clarity, the various parts in the accompanying drawings are not drawn to scale. In addition, some well-known parts may not be shown in the drawings.
[0061] The all-solid-state calcium ion selective electrode suitable for concrete of the present invention comprises a conductor 1, an electronic conductor 2, a Fe3O4@CNTs transduction layer 3, a calcium ion selective membrane 4, and a shell 5; the upper section and the upper part of the electronic conductor 2 are connected to the inner wall of the shell 5 by a fixing material (epoxy resin) 6, and play a packaging role. The lower end of the conductor 1 is connected to the upper end of the electronic conductor 2, the Fe3O4@CNTs transduction layer 3 is loaded on the lower end surface of the electronic conductor 2, and the calcium ion selective membrane 4 is loaded on the end surface of the Fe3O4@CNTs transduction layer 3, and then placed in the shell 5, and the upper section and the upper part of the electronic conductor 2 are connected to the inner wall of the shell 5 by the fixing material 6 and packaged;
[0062] The conductor 1 is a copper wire, the electronic conductor 2 is a pre-treated copper rod electronic conductor, and the shell 5 is a PC tube.
[0063] Embodiment 1
[0064] The conductor is copper wire;
[0065] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0066] The preparation of Fe3O4@CNTs includes the following steps:
[0067] (1) Pour CNTs into 0.45 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0068] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at a speed of 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 55° C. to obtain CNTs;
[0069] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0070] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0071] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0072] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0073] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0074] (1) Connect the upper end of the copper rod to the wire;
[0075] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 50 μm was obtained;
[0076] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 30 μm;
[0077] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0078] Embodiment 2
[0079] The conductor is copper wire;
[0080] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 12 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 12 minutes, and finally use deionized water ultrasonic cleaning for 12 minutes, and dry for use.
[0081] The preparation of Fe3O4@CNTs includes the following steps:
[0082] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 60 °C for 1.5 h, and cool them naturally to room temperature to obtain mixture I;
[0083] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0084] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0085] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0086] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0087] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0088] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0089] (1) Connect the upper end of the copper rod to the wire;
[0090] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 50 μm was obtained;
[0091] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 40 μm;
[0092] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0093] Embodiment 3
[0094] The conductor is copper wire;
[0095] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 15 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 15 minutes, and finally use deionized water ultrasonic cleaning for 15 minutes, and dry for use.
[0096] The preparation of Fe3O4@CNTs includes the following steps:
[0097] (1) Pour CNTs into 0.55 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 65 °C for 2 h, and cool them naturally to room temperature to obtain mixture I;
[0098] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0099] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0100] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0101] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0102] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0103] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0104] (1) Connect the upper end of the copper rod to the wire;
[0105] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 50 μm was obtained;
[0106] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0107] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0108] Embodiment 4
[0109] The conductor is copper wire;
[0110] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0111] The preparation of Fe3O4@CNTs includes the following steps:
[0112] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0113] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0114] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0115] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0116] (5) The mixture was centrifuged at 7000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0117] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0118] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0119] (1) Connect the upper end of the copper rod to the wire;
[0120] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 60 μm was obtained;
[0121] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0122] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0123] Embodiment 5
[0124] The conductor is copper wire;
[0125] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0126] The preparation of Fe3O4@CNTs includes the following steps:
[0127] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 4 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0128] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0129] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0130] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0131] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0132] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0133] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0134] (1) Connect the upper end of the copper rod to the wire;
[0135] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the above mixture was coated on the lower end section of a copper rod, and after the organic solvent was completely evaporated, the coating was continued; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 70 μm was obtained;
[0136] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0137] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0138] Embodiment 6
[0139] The conductor is copper wire;
[0140] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0141] The preparation of Fe3O4@CNTs includes the following steps:
[0142] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 5 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0143] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at a speed of 9000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0144] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0145] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0146] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0147] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0148] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0149] (1) Connect the upper end of the copper rod to the wire;
[0150] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 80 μm was obtained;
[0151] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0152] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0153] Embodiment 7
[0154] The conductor is copper wire;
[0155] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0156] The preparation of Fe3O4@CNTs includes the following steps:
[0157] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0158] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0159] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0160] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0161] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0162] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0163] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0164] (1) Connect the upper end of the copper rod to the wire;
[0165] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 90 μm was obtained;
[0166] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0167] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0168] Embodiment 8
[0169] The conductor is copper wire;
[0170] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0171] The preparation of Fe3O4@CNTs includes the following steps:
[0172] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0173] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0174] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0175] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0176] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0177] Preparation of calcium ion selective membrane: 1.656 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0178] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0179] (1) Connect the upper end of the copper rod to the wire;
[0180] (2) Add 100 mg of Fe3O4@CNTs and 5 mg of DOP to 1 mL of 1.0% ethanol solution and disperse by ultrasonic for 30 min to obtain a uniform mixture; apply the mixture to the lower end section of a copper rod, and then apply the mixture again after the organic solvent is completely evaporated; repeat the process several times to obtain a Fe3O4@CNTs transduction layer with a thickness of 100 μm;
[0181] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0182] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0183] Embodiment 9
[0184] The conductor is copper wire;
[0185] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0186] The preparation of Fe3O4@CNTs includes the following steps:
[0187] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0188] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0189] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0190] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0191] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0192] Preparation of calcium ion selective membrane: 1.6 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0193] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0194] (1) Connect the upper end of the copper rod to the wire;
[0195] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 50 μm was obtained;
[0196] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0197] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0198] Embodiment 10
[0199] The conductor is copper wire;
[0200] Pretreatment of the electronic conductor copper rod: first use acetone ultrasonic cleaning for 10 minutes, then use 0.1 mol / L dilute hydrochloric acid solution ultrasonic cleaning for 10 minutes, and finally use deionized water ultrasonic cleaning for 10 minutes, and dry for use.
[0201] The preparation of Fe3O4@CNTs includes the following steps:
[0202] (1) Pour CNTs into 0.5 mol / L nitric acid and disperse them by ultrasonic for 3 h, then pour them into a reactor, keep the temperature at 60°C for 1 h, and cool them naturally to room temperature to obtain mixture I;
[0203] (2) treating the mixture I with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and when the pH of the solution is 7, centrifuging the mixture at 8000 r / min to separate the solid matter from the deionized water, and vacuum drying the mixture at 60° C. to obtain CNTs;
[0204] (3) 0.80 g FeCl2·4H2O and 0.70 g SnCl4·5H2O (Fe / Sn is 2:1 molar ratio) were dissolved in 40 mL deionized water, followed by adding 0.07 g CNTs, ultrasonically dispersed for 10 min, and 2.4 g NaOH (2 M) was added dropwise under vigorous stirring to obtain mixture II;
[0205] (4) Transferring mixture II to a reactor and maintaining the temperature at 240° C. for 24 h to obtain mixture III;
[0206] (5) The mixture was centrifuged at 8000 r / min for 10 min, and the solid matter was collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
[0207] Preparation of calcium ion selective membrane: 1.7 mg calcium ion carrier ETH 5234, 1.728 mg ion exchanger NaTFPB, 118.872 mg polymer PVC matrix, 237.744 mg plasticizer o-NPOE were added into a container, followed by 1.8 mL redistilled THF, and stirred evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
[0208] A preparation method of an all-solid-state calcium ion selective electrode suitable for concrete comprises the following steps:
[0209] (1) Connect the upper end of the copper rod to the wire;
[0210] (2) 100 mg of Fe3O4@CNTs and 5 mg of DOP were added to 1 mL of 1.0% ethanol solution and ultrasonically dispersed for 30 min to obtain a uniform mixture; the mixture was coated on the lower end section of a copper rod, and the coating was continued after the organic solvent was completely evaporated; after repeating the process several times, a Fe3O4@CNTs transduction layer with a thickness of 50 μm was obtained;
[0211] (3) The calcium ion selective membrane is loaded on the Fe3O4@CNTs transduction layer with a thickness of about 50 μm;
[0212] (4) The wire, copper rod, Fe3O4@CNTs transfer layer, and calcium ion selective membrane connected as a whole are placed in the outer shell, and the upper section of the copper rod and the part above it are fixed to the inner wall of the outer shell by a fixing material, thereby obtaining an all-solid-state calcium ion selective electrode suitable for concrete.
[0213] Performance Testing
[0214] A saturated calomel electrode was used as a reference electrode to prepare sodium hydroxide solutions of different concentrations, and the open circuit potential of the all-solid-state calcium ion selective electrode suitable for concrete of the present invention was tested at different pH values.
[0215] The different selective electrodes in Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7 and Example 8 were added with 10% water per liter of deionized water. 0 -10 -6 mol of CaCl2, place a calcium ion selective electrode and a saturated calomel electrode in the solution to measure their open circuit potential, and calculate the slope of their response curve.
[0216] Prepare NaOH solutions with pH values of 7, 8, 9, 10, 11, and 12, and then add 10 3 mol of CaCl2, the calcium ion selective electrode and the saturated calomel electrode in Example 3 were placed in the solution for 3 h and their open circuit potentials were continuously measured to record their offsets.
[0217] Figure 2 The relationship between the open circuit potential of the electrode and the logarithm of the negative concentration of calcium ions when the pH is 7 in Example 3 (the thickness of the calcium ion selective membrane is 50 μm), the fitting equation is y=46.4x-439.2, R 2 =0.98448, where y is the open circuit potential and x is the negative logarithm of the calcium ion concentration. Fitting curve R 2 It is 0.98448, indicating that the fitting curve has a very high goodness of fit and the fitting equation is reliable.
[0218] Figure 3 The relationship between the open circuit potential of the electrode and the logarithm of the negative concentration of calcium ions when the pH is 7 in Example 2 (the thickness of the selective membrane is 40 μm), the fitting equation is y=42.1x-423.5, R 2 =0.9549, where y is the open circuit potential and x is the negative logarithm of the calcium ion concentration. Fitting curve R 2 It is 0.9549, indicating that the fitting curve has a high goodness of fit and the fitting equation is reliable.
[0219] Figure 4The relationship between the open circuit potential of the electrode and the logarithm of the negative concentration of calcium ions when the pH is 7 in Example 1 (the thickness of the selective membrane is 30 μm), the fitting equation is y=40.9x-166.1, R 2 =0.98356, where y is the open circuit potential and x is the negative logarithm of the calcium ion concentration. Fitting curve R 2 It is 0.98356, indicating that the fitting curve has a high goodness of fit within the range shown in the figure, and the fitting equation is reliable, indicating that the all-solid-state calcium ion selective electrode of the present invention is relatively reliable, has good ion conductivity, and has good workability.
[0220] The all-solid-state calcium ion selective electrode in Example 3 was used as the working electrode, the saturated calomel electrode as the reference electrode, and the platinum electrode as the auxiliary electrode in 0.1 mol / LCaCl2, and then connected to the electrochemical workstation, and a chronopotentiometry test was performed under the condition of plus or minus 1 nA. The test results Figure 5 As shown, the potential difference is small, indicating that its stability is good.
[0221] Table 1 shows the slopes of the curves of different transduction layer thicknesses and potential responsiveness and the reliability R obtained in the tests of Example 3, Example 4, Example 5, Example 6, Example 7, and Example 8. 2 The table (selective membrane thickness is 50μm) shows that the responsiveness of the sensor is optimal when the transduction layer thickness is 100μm, but the responsiveness is not much different. Considering the cost, electrodes with a transduction layer thickness of 50μm are selected for other experiments.
[0222] Table 1 Slope and reliability of different transduction layer membrane thickness and potential responsiveness curves obtained in the tests of Example 3, Example 4, Example 5, Example 6, Example 7, and Example 8
[0223]
[0224] Table 2 is a table showing the relationship between the potential shift after immersion in solutions of different pH values for 1 hour, obtained by using the selective electrode test in Example 3. It can be seen from the table that the potential shift is low, and when the pH value rises, the potential shift will gradually increase, but still remain at a low level. This indicates that it has good alkali resistance and is suitable for concrete.
[0225] Table 2 Relationship between potential shifts after immersion in solutions of different pH values for 1 hour obtained from the selective electrode test in Example 3
[0226]
[0227] Table 3 shows the response curve slopes of the selective electrodes prepared by using the selective membranes of different ratios described in Example 3, Example 9 and Example 10 in the solution and the response curve slopes of the selective electrodes prepared by using the separate solution method, i.e., soaking in a 0.001 mol / L magnesium chloride solution for one day and then placing in a solution of 10 -1 , 10 -2 , 10 -3 The selectivity coefficients for various cations prepared and measured in mol / L MgCl2, KCl, NaCl and CaCl2 solutions show that the electrode has good selectivity and good working performance.
[0228] Table 3 Response curve slopes of the selective electrodes described in Example 3, Example 9 and Example 10 in solution and selectivity coefficients for various cations
[0229] Embodiment 9 Embodiment 3 Embodiment 10 Calcium ion carrier amount (g) 1.6 1.656 1.7 Slope 43.7 46.4 38.9 <![CDATA[Mg 2+ Selectivity coefficient]]> 4.9 5.3 5.5 <![CDATA[Na 2+ Selectivity coefficient]]> 3.72 4.36 4.4 <![CDATA[K 2+ Selectivity coefficient]]> 3.95 4.6 4.8
Claims
1. An all-solid-state calcium ion selective electrode suitable for concrete, characterized in that: The invention comprises a conductor (1), an electronic conductor (2), a Fe3O4@CNTs transduction layer (3), a calcium ion selective membrane (4), an outer shell (5) and a fixing material (6), wherein the conductor (1), the electronic conductor (2), the Fe3O4@CNTs transduction layer (3) and the calcium ion selective membrane (4) are sequentially connected from top to bottom to form a whole and are placed in the outer shell (5), and the upper section of the conductor is located outside the outer shell, and the upper section of the electronic conductor and the lower section of the conductor are encapsulated with the outer shell by the fixing material (6); The lower end of the wire is connected to the upper end of the electronic conductor, the lower end of the electronic conductor is coated with Fe3O4@CNTs to form a Fe3O4@CNTs transduction layer, and the calcium ion selective membrane is loaded below the Fe3O4@CNTs transduction layer; The preparation method of the calcium ion selective membrane is as follows: adding calcium ion carrier ETH5234, ion exchanger NaTFPB, polymer PVC matrix and plasticizer o-NPOE into a container, then adding redistilled THF, and stirring evenly at room temperature to obtain a calcium ion selective membrane with uniform concentration.
2. The all-solid-state calcium ion selective electrode suitable for concrete according to claim 1, characterized in that: The preparation method of Fe3O4@CNTs comprises the following steps: (1) Pour CNTs into acid for ultrasonic dispersion, pour into a reaction kettle, keep constant temperature at 55-65°C for 1-2 hours, and cool naturally to room temperature to obtain mixture I; (2) treating the mixture obtained in step (1) with an ultrasonic generator for 1 h, diluting and filtering the mixture several times with deionized water, and centrifuging the mixture when the pH value of the solution is between 6.5 and 7.5 to separate the solid matter from the deionized water, and vacuum drying the mixture to obtain CNTs; (3) dissolving FeCl2·4H2O and SnCl4·5H2O in deionized water, then adding the CNT obtained in step (2), and ultrasonically dispersing for at least 10 min, and adding NaOH solution dropwise under vigorous stirring to obtain mixture II; (4) transferring the mixture II obtained in step (3) into a reaction vessel to react and obtain a mixture III; (5) The mixture III obtained in step (4) is centrifuged, and the solid matter is collected, washed with deionized water for multiple times and vacuum dried to obtain Fe3O4@CNT.
3. The all-solid-state calcium ion selective electrode suitable for concrete according to claim 2, characterized in that: In step (1), the acid is nitric acid or a mixed solution of nitric acid and sulfuric acid, wherein the concentration of the acid is 0.45-0.55 mol / L; the ultrasonic dispersion time is 3-5 h; The centrifugal speed in step (2) is 7000-9000 r / min, and the vacuum drying temperature is 55-65° C.; The concentration of the NaOH solution in step (3) is 2 mol / L, and the mass fractions of each raw material component are: The above-mentioned NaOH mass fraction is the solubility in the NaOH solution. And the molar ratio of Fe / Sn must be 2:1; In step (4), the reaction temperature is 230-245° C. and the reaction time is 18-30 h; In step (5), the centrifugal speed is 7000-9000 r / min, and the centrifugal time is 10-15 min.
4. The all-solid-state calcium ion selective electrode suitable for concrete according to claim 1, characterized in that: The preparation method of the calcium ion selective membrane is as follows: the mass fractions of the raw material components are as follows:
5. The all-solid-state calcium ion selective electrode suitable for concrete according to any one of claims 1 to 4, characterized in that: The lower end of the wire and the upper end of the electronic conductor are connected by high-temperature welding or conductive adhesive bonding, and the wire is a copper wire; The fixing material is epoxy resin; The electronic conductor uses a copper rod electronic conductor, a pretreated copper rod electronic conductor, and a metal or glassy carbon electrode as the electronic conductor material; The shell is made of PC material and is in a tubular shape.
6. An all-solid-state calcium ion selective electrode suitable for concrete according to any one of claims 1 to 4, characterized in that: The thickness of the calcium ion selective membrane is 30 to 50 μm; The Fe3O4@CNTs transduction layer has a thickness of 50 to 100 μm.
7. The all-solid-state calcium ion selective electrode suitable for concrete according to claim 5, characterized in that: The pretreatment method of the pretreated copper rod electronic conductor comprises: firstly using acetone to ultrasonically clean the copper rod electronic conductor for 10 to 15 minutes, then using 0.1 mol / L dilute hydrochloric acid solution to ultrasonically clean it for 10 to 15 minutes, then using deionized water to ultrasonically clean it for 10 to 15 minutes, and finally drying it.
8. A method for preparing an all-solid-state calcium ion selective electrode suitable for concrete according to any one of claims 1 to 7, characterized in that: The specific steps include: (1) Connecting the upper end of the electronic conductor to the lower end of the wire; (2) adding Fe3O4@CNTs to an organic solvent and dispersing by ultrasonic to obtain a uniform mixture; then coating the mixture on the lower end of the electronic conductor, and coating again after the organic solvent is completely volatilized; repeating the process 2-3 times to obtain a Fe3O4@CNTs transduction layer; The organic solvent in step (2) is a mixture of DOP and 0.1% ethanol solution; The amounts of the components in step (2) are: 20 parts by mass of Fe3O4@CNTs, 1 part by mass of organic solvent; The ultrasonic dispersion time in step (2) is 30 to 40 minutes; (3) loading the calcium ion selective membrane on the Fe3O4@CNTs transduction layer obtained in step (2); (4) Finally, the wire, the electronic conductor, the Fe3O4@CNTs transduction layer, and the calcium ion selective membrane connected as a whole are placed in the outer shell, the upper section of the electronic conductor and the upper part are fixed to the inner wall of the outer shell by a fixing material, and the upper section of the wire is exposed outside the outer shell, thus obtaining the all-solid-state calcium ion selective electrode.
9. A method for applying the all-solid-state calcium ion selective electrode suitable for concrete according to any one of claims 1 to 7, characterized in that: The all-solid-state calcium ion selective electrode is suitable for use in existing concrete buildings and new buildings.
10. The application method according to claim 9, characterized in that: When the all-solid-state calcium ion selective method is applied to existing concrete buildings, a hole is drilled in advance in the concrete to be tested, the depth of the hole is the depth of the concrete to be tested, the all-solid-state calcium ion selective electrode is placed in a tube, the electrode is fixed in a detachable manner, the bottom of the electrode shell is in contact with the bottom of the hole, and a solid reference electrode is inserted to form a dual-electrode system, so that the calcium ion concentration of the concrete can be detected and monitored; When the all-solid-state calcium ion selective electrode is applied to a newly built building, before pouring concrete, a certain length of tubes made of materials such as stainless steel and PC, with a diameter slightly larger than the maximum diameter of the electrode, with the bottom ends of the tubes at an equal distance from each other, are pre-installed at the position to be tested as a mold, and the bottom of the tube is blocked with an easily removable non-absorbent rod-shaped object, and then concrete is poured; after the construction is completed, the non-absorbent rod-shaped object in the tube is taken out, and the all-solid-state calcium ion selective electrode is placed in the tube, and the electrode is fixed in a detachable manner, so that the bottom of the electrode contacts the bottom of the hole, and the calcium ion concentration of the concrete can be detected and monitored.
Citation Information
Patent Citations
All-solid reference electrode for monitoring steel bar corrosion of concrete and its preparation method
CN101144790A
Preparation and application of all-solid-state calcium ion selective electrode transduction layer electrode material
CN112374549A
All-solid-state calcium ion selective electrode, preparation method thereof and application of all-solid-state calcium ion selective electrode in blood gas analysis and detection
CN116183696A
All-solid-state calcium ion selective electrode based on high-hydrophobicity copper sulfide and application of all-solid-state calcium ion selective electrode
CN116953049A
Chloride ion sensor suitable for concrete
CN117491453A